Análise numérico-experimental de flambagem lateral com torção e de ligações em vigas com perfis de alma corrugada senoidal - Lourdiane Gontijo das Merces Gonzaga (2008)
The usage of corrugated web profiles has been growing during recent years due to reduction of the structural self weight and to automation of the productive process of these profiles. Because the construction process and automation of production are relatively new, most information is only available in publications. The codes are stillinsufficient to cover all the application possibilities of these profiles. In order to improve and to complement the available information and rules, some researches are being developed at UFMG, concerning the application of sinusoidally corrugated web profiles in steel construction and in composite steel-concrete construction. The present work is part of this research and the target is the proposal of design procedures for theanalysis of lateral torsional buckling and a type of end connection of sinusoidally corrugated web profiles. The proposed procedures were evaluated by parametric analyses, with results obtained from finite element models, showing good conformity. Validation of the finite element models was made through experimental tests. The proposed procedures can be used for the calculation and design of lateral torsionalbuckling and end connections of sinusoidally corrugated beams, both in steel construction or the initial stage of unshored composite constructions.